PEMIDANAAN TINDAK PIDANA KEALPAAN YANG MENYEBABKAN MATINYA ORANG LAIN DALAM KECELAKAAN LALU LINTAS SETELAH KELUARNYA UNDANG-UNDANG NOMOR 22 TAHUN 2009 - A.M. Endah Sri Astuti, Amaretza Lucky R.L.P.*, Pujiyono, (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2014)
The number of traffic accidents and the number of casualties and material losses caused by traffic accidents, making the government issued new rules regarding traffic. It is characterized by the enactment of Law No. 22 of 2009 on Road Traffic and Road Transportation. With the enactment of Law No. 22 of 2009, the expected number of traffic violations and accidents is lowered. After the release of Law No. 22 of 2009, punishment about criminal negligence that caused the death of another person in a traffic accident in Semarang District Court using Article 310 paragraph (4) of Law No. 22 of 2009, no longer using Article 359 of the Criminal Code (KUHP). Law No. 22 of 2009 more than the base used in the present Criminal Code, because the Law No. 22 of 2009 is more specific and itâ€™s a special law which only governs the crime of traffic.Key Words : Punishment, Negligence That Caused The Death of Another Person, Traffic AccidentÂ